Increasing stomatal conductance in response to rising atmospheric CO2. (31st January 2018) - Purcell, C; Batke, S P; Yiotis, C; Caballero, R; Soh, W K; Murray, M; McElwain, J C
Abstract: Background and Aims: Studies have indicated that plant stomatal conductance ( g s ) decreases in response to elevated atmospheric CO2, a phenomenon of significance for the global hydrological cycle. However, g s increases across certain CO2 ranges have been predicted by optimization models. The aim of this work was to demonstrate that under certain environmental conditions, g s can increase in response to elevated CO2 . Methods: Using (1) an extensive, up-to-date synthesis of g s responses in free air CO2 enrichment (FACE)experiments, (2) in situ measurements across four biomes showing dynamic g s responses to a CO2 rise of 50 ppm (characterizing the change in this greenhouse gas over the past three decades) and (3) a photosynthesis–stomatal conductance model, it is demonstrated that g s can in some cases increase in response to increasing atmospheric CO2 . Key Results: Field observations are corroborated by an extensive synthesis of g s responses in FACE experiments showing that 11.8 % of g s responses under experimentally elevated CO2 are positive. They are further supported by a strong data-model fit ( r 2 = 0.607) using a stomatal optimization model applied to the field g s dataset. A parameter space identified in the Farquhar–Ball–Berry photosynthesis–stomatal conductance model confirms field observations of increasing g s under elevated CO2 in hot dry conditions. Contrary to the general assumption, positive g s responses to elevated CO2, although relatively rare, are a feature of woody taxa adapted to warm, low-humidity conditions, and this response is also demonstrated in global simulations using the Community Land Model (CLM4). Conclusions: The results contradict the over-simplistic notion that global vegetation always responds with decreasing g s to elevated CO2, a finding that has important implications for predicting future vegetation feedbacks on the hydrological cycle at the regional level.